A single system image server cluster using duplicated MAC and IP addresses - Vaidya, S.; Christensen, K.J. (Proceedings LCN 2001. 26th Annual IEEE Conference on Local Computer Networks, 2001)
Clusters of PCs are increasingly being used to build high-capacity Web sites. We develop and evaluate a method of building a single system image (SSI) cluster that does not require a central dispatcher. In our clone cluster method, which builds on the existing ONE-IP method, a group of mirrored server machines with identical MAC and IP addresses are configured on a shared-medium LAN. Each machine filters incoming IP packets based on a hash of IP source addresses. Unlike ONE-IP, our method does not require router configuration changes. We build and evaluate a Linux-based, two-PC cluster that uses an odd/even filter. Simulation results show that the effect of server selection method on mean response time is less significant for heavy-tailed interarrival times than for exponential interarrival times. Simulation results show that response time performance from a Clone Cluster can be very close to that of a centrally dispatched least-loaded cluster.